Turning Boycott into a Sustainable Opportunity: Leveraging Boycott to Boost Local Production and Enhance Local Market Competitiveness in Egypt - Maher, Alaa (AUC Knowledge Fountain, 2026)
While existing literature largely concentrates on the consumer behavior dimensions of boycotts, limited attention has been paid to their structural economic implications for FDI and local production. This paper frames the 2023 boycott campaign as a demand shock in Egypt’s food and beverages sector. Dependency theory is applied to assess the pre-boycott stage, where MNCs’ market power created structural dependencies within the sector. Dynamic capabilities theory is employed to explain the heterogeneity in firm responses during the boycott and their attempts to acquire sustainable market share. Using a multi-case study design, qualitative in-depth interviews were conducted across 16 firms in the sector, accounting for variations in firm size and maturity stage. The study explores the perceptions of senior managers and operators regarding the boycott-induced demand surges and how it altered the market dynamics. It also examines the strategic decisions implemented in key functional areas to enhance firm growth and competitiveness. Findings reveal that sales and/or brand visibility of participating firms have improved during the boycott. Strategic decisions have been witnessed in firm expansion, product and value proposition, marketing and branding, supplier substitution, hiring, and increased localization efforts. Insights of the study are then utilized to develop a policy framework integrating firm-level adaptation with national strategic goals of import substitution and strengthening local production.